ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS KONSUMEN PADA MEREK STARBUCKS DI WILAYAH JAKARTA DAN SEKITARNYA - Yokie Radnan Kristiyono; Aisyah Rahmi; Mington Triwijaya Triwijaya; Riandi Gantha Suhanda (Universitas Multimedia Nusantara, 2020)
One of the factors in the movement of the economy in Indonesia is supported by the development of new businesses, one of which is a coffee beverage business. Coffee drinks business in Indonesia is one of the fastest growing business. Developments in the business sector can be seen from the emergence of enhancement of new starbucks coffee shops . The top-leading coffee shop in the Indonesian market today is Starbucks, it is shown by numbers of Starbucks’ branches located almost in the entire region of Indonesia. The factor that makes Starbucks one of the strongest brand is the presence of customers who became loyal to the brand and make Starbucks as their first choice. The other factors that also affect the customer loyalty towards Starbucks are Brand Image, Brand Experience, Customer Satisfaction, Brand Trust, and Brand Love. Therefore, this research aims to examine the determinant factors of building customer loyalty of Starbucks’ customers in Jakarta and surrounding areas. The method of analysis used by researchers in this study was SmartPLS 3.0 with 150 respondents who have enjoyed Starbucks coffee. In this study there were nine hypotheses supported by previous researches. In the results of this study, there were six hypotheses accepted and three hypotheses were rejected. Through this research, researchers hope to provide benefits for the reader especially for those who want to know about the factors that affect the customer loyalty of Starbucks in Jakarta and its surrounding areas. Key Words: Brand Image, Brand Experience, Customer Satisfaction, Brand Trust, BrandLove. Customer Loyalty, Starbucks